THE PRINCIPAL'S SUPERVISION OBSERVATIONAL APPROACH TOWARDS TEACHERS’ PERFORMANCE AT SDN 12 BANTAN KABUPATEN BENGKALIS - Sumiati Sumiati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
School action research is a research that aims to improve learning methods and improve the results of the learning process in schools. This research was conducted at SDN 12 Bantan, Kecamatan Bantan, Kabupaten Bengkalis. The subject of this research was the teachers at SDN 12 Bantan. This research method was a descriptive method aiming to explain or describe the facts found in the field. The approach taken in this study was observational supervision which functioned to monitor and improve the teachers ability in the learning process in order to achieve the objectives of the learning. The results showed an increase in teachers’ activity during the learning process in the first cycle of the first meeting with the percentage of 62% with fairly good category. Then, in the first cycle at the second meeting, the percentage of teacher activity during the learning process increased to 64% which was still in fairly good category. Therefore, it was continued to learning reflection in the second cycle of the third meeting, and the percentage of teachers’ activity in the learning process was 88% with very good category. After that, it was continued to the fourth meeting in which the percentage of teacher activity in the learning process was 96% with very good category. Then, the results of teachers’ performance observations after the application of learning reflection in the form of educational supervision observations carried out in 2 cycles, it was found that the teachers began to be able to master and understand the teaching materials well, were able to explain the material, and were able to build a communicative atmosphere in the classroom, enjoyed what they taught and liked teaching as a profession, understood students, their experiences, abilities and achievements, used various methods in teaching so that students did not get bored with the old method, were able to eliminate materials that were less important and less meaningful, always followed the latest developments in knowledge. The learning process was always prepared, encouraging students to obtain better results. That meant teachers were able to develop their abilities and were able to apply them well.